Managing quality strategic issues in health care management - Davies, Huw T. O. 1961-; Tavakoli, Manouche; Malek, Mohamed H. 1949-2001; Neilson, Aileen R. (Routledge, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- List of Tables -- Acknowledgments -- Preface -- Section 1: Scene Setting -- 1 Is Health Care a Business? An Analysis of Health Care, and its Consideration as a Business -- 2 Managing the Design of Health Care Services -- Section 2: Quality in Health Care -- 3 Towards Critical Quality -- 4 Whose Quality? Different Interest Groups' Perspectives on Health Care Quality -- 5 The Quantification of Patient Satisfaction -- 6 Managing Clinical Audit: Diagnosing the Problems and Designing Solutions -- 7 Improving Child Dental Health in Scotland: An Audit in Primary Care -- 8 Human Resource Management Audits: Contributions to Quality -- Section 3: Using Performance Indicators -- 9 What Are We Counting with Hospital Episode Statistics (HES)? -- 10 Clinical Outcomes Indicators in Scotland: Lessons and Prospects -- 11 What do Managers and Physicians Prefer as Indicators of Clinical Outcome? -- 12 Performance Indicators: A Patient-centred Approach -- 13 Is Indicator Use for Quality Improvement and Performance Measurement Compatible? -- 14 Published Health Outcomes: Guiding Lights or Wreckers' Lanterns? -- List of Contributors
Keywords: Gesundheitswesen; Qualitätsmanagement; Konferenzschrift